Preparation method of high-orientation CuFeTe2 film for solar cell

Preparing high-oriented CuFeTe2 thin films by electrodeposition method solves the challenges of existing solar cell materials in improving photoelectric conversion efficiency and reducing material costs, and significantly improves the crystal structure of the film and the performance of solar cells.

CN119663391APending Publication Date: 2025-03-21BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575167.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing solar cell materials have challenges in improving photoelectric conversion efficiency and reducing material costs, especially in optimizing P-type absorbing layer materials and their preparation methods.

Method used

Electrodeposition method is used to prepare high-oriented CuFeTe2 films. By controlling process parameters such as electrochemical potential and current, the thickness, chemical composition and crystal structure of the film are accurately controlled, and heat treatment is carried out to optimize the film performance.

Benefits of technology

The crystal structure of the CuFeTe2 film is significantly improved, making the film continuously dense within a certain range, and improving the performance and efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663391A_ABST
    Figure CN119663391A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-orientation CuFeTe2 thin film for a solar cell, which belongs to the technical field of solar cells and comprises the following steps: an FTO (Fluorine-doped Tin Oxide) base cleaning step and an electro-deposition solution preparation step, a constant-potential deposition step: under atmospheric pressure, using a constant-potential three-electrode system to place the FTO base in an electro-deposition solution for electro-deposition, presetting deposition temperature, deposition time and deposition potential, the deposition potential being-1.0 V; wherein the FTO base is a working electrode, the saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of an electrodeposition solution is controlled by a water bath method; and cleaning and annealing. According to the method, the CuFeTe2 thin film is prepared through electro-deposition, the deposition potential is optimized, so that the CuFeTe2 thin film forms preferred orientation on the crystal face (101), the crystal structure of the thin film is remarkably improved, the thin film is continuous and compact within a certain range, and the deposition effect is optimal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar energy technology and relates to a highly oriented CuFeTe 2 Film preparation method. Background Art

[0002] In recent years, the use of non-renewable energy such as coal, oil, and natural gas has increased. Large-scale mining and use will make humans face the crisis of non-renewable energy depletion, and will also bring certain environmental pollution problems and aggravate the greenhouse effect. Based on this, the development of new energy is particularly important. As an inexhaustible renewable energy source, solar energy has attracted widespread attention. Solar cells are devices that convert sunlight into electrical energy, and their development history can be traced back to the 19th century. With the development of science and technology, solar cell technology has been continuously optimized, and many types of solar cells have emerged, such as silicon-based solar cells, cadmium telluride (CdTe) thin film cells, copper indium gallium selenide (CIGS) thin film cells, copper zinc tin sulfur (CZTS) thin film cells, gallium arsenide (GaAs) thin film cells, dye-sensitized thin film cells, etc.

[0003] Although there are many types of existing solar cells, they all have corresponding problems, because new thin-film solar cell materials need to be developed to further improve the photoelectric conversion efficiency and reduce material costs, such as optimizing the material of the P-type absorption layer and matching the corresponding preparation method of the P-type absorption layer, such as: chemical co-reduction, magnetron sputtering, vacuum evaporation, hydrothermal or electrodeposition method preparation. CuFeTe 2 It is a typical two-dimensional ternary transition metal silicide, which exhibits fuzzy magnetic behavior and spin density wave characteristics in the ground state. This is a very narrow band gap, which can even reach 0 band gap. CuFeTe 2 It is a tetragonal crystal with lattice constants a=b=3.934A, c=6.078A, and p=P4 / nmm. CuFeTe 2 It is a promising P-type semiconductor material.

[0004] Since the absorption layer material has certain requirements on the proportion of its composition, different preparation methods will lead to different compositions and structures of the prepared films, thus producing different electrical and optical properties, leading to changes in battery efficiency.

[0005] Based on the above research, it is necessary to provide a highly oriented CuFeTe 2 Film preparation method. Summary of the invention

[0006] The object of the present invention is to provide a highly oriented CuFeTe 2The electrodeposition method is a process of depositing materials on electrodes using an external power source. The quality of the film is ensured by controlling the electrochemical potential, current and other process parameters, and the thickness, chemical composition and crystal structure of the film are precisely controlled. 2 The good performance of CuFeTe was prepared by heat treatment after electrodeposition. 2 film.

[0007] Flow chart of electrodeposition preparation of copper iron tellurium thin film. Electrodeposition preparation process: experimental drug preparation - FTO base cleaning (preparation of electrodeposition solution) - constant potential deposition - heat treatment - target product film.

[0008] FTO base cleaning: The main cleaning process of FTO substrate is as follows: S1: Use medical cloth to clean the FTO base to remove dust and grease remaining on its surface; S2: Put the FTO base into a detergent solution for ultrasonic cleaning for 10 minutes; S3: Put the FTO base into deionized water for ultrasonic cleaning for 10 minutes; S4: Then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 for ultrasonic cleaning for 10 minutes; S5: Put it into anhydrous ethanol for ultrasonic shock for 10 minutes; S6: Finally, put the cleaned FTO base into anhydrous ethanol for storage, wrap the beaker mouth with plastic wrap and seal it.

[0009] Preparation of electrodeposition solution: The steps for preparing the electrodeposition solution are as follows: weighing the drug using an analytical balance, dissolving tellurium dioxide in hydrochloric acid, using a magnetic stirrer to heat and stir the solution to accelerate its dissolution, and after the dissolution is completed, adding deionized water to a preset scale, and then adding sodium citrate, FeCl2 and CuSO4, fully dissolving them, and finally obtaining an electrodeposition solution.

[0010] Sample preparation and preservation, heat treatment: The film was prepared at atmospheric pressure and electrodeposited using a three-electrode system with constant potential. The FTO glass substrate was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the electrode was a platinum electrode. According to different research schemes, the electrodeposition solution was configured, and the temperature of the solution during the deposition process was controlled by a water bath. At the end of the deposition, the substrate coated with the target product was removed from the precipitation solution, soaked in deionized water three times, and then dried in an incubator. The sample was sealed in a steel reactor and annealed at a fixed temperature and time. After annealing, the sample was cooled to room temperature and stored in a sample bag.

[0011] To achieve the purpose of the invention, the present invention adopts the following technical solution: highly oriented CuFeTe 2 The method for preparing a thin film is characterized by comprising the following steps: FTO substrate cleaning step and electrodeposition solution preparation step: the electrodeposition solution comprises; Constant potential deposition step: under atmospheric pressure, the FTO base is placed in an electrodeposition solution for electrodeposition using a constant potential three-electrode system, and the deposition temperature, deposition time and deposition potential are preset, and the deposition potential is -1.0V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing steps: The sample treated by the constant potential deposition step is immersed in deionized water for 3 times, then taken out and annealed at a preset temperature and a preset time to prepare CuFeTe 2 film.

[0012] FTO base cleaning includes: S1: Use a medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the beaker mouth is wrapped with plastic wrap and sealed. The steps of preparing the electrodeposition solution are to weigh the drug using an analytical balance, dissolve tellurium dioxide in hydrochloric acid, use a magnetic stirrer, stir and dissolve while heating to accelerate its dissolution, and after the dissolution is completed, add deionized water to the preset scale, and then add sodium citrate, FeCl2 and CuSO4, fully dissolve, and finally obtain the electrodeposition solution.

[0013] Preferably, the deposition time of the constant potential deposition step is 20 min.

[0014] Preferably, the deposition temperature of the constant potential deposition step is 30° C. and the deposition time is 20 min.

[0015] Preferably, the deposition temperature of the constant potential deposition step is 50° C. and the deposition time is 20 min.

[0016] Preferably, CuFeTe 2 The thickness of the film was 20 μm.

[0017] Preferably, the deposition temperature of the constant potential deposition step is 90° C. and the deposition time is 20 min.

[0018] Preferably, in the annealing step, the preset temperature is 200° C., and the preset time is 30 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The solar cell of the present invention is a kind of solar cell based on copper iron telluride (CuFeTe 2 ) thin film solar cells. CuFeTe 2 It is a layered material with p-type semiconductor characteristics. By optimizing the deposition potential, CuFeTe 2 The film forms a preferred orientation on the (101) crystal plane, which significantly improves the crystal structure of the film, making the film continuous and dense within a certain range and achieving the best deposition effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Shows the XRD patterns of films with different deposition times (10 min to 30 min) when the deposition potential is -1.0 V.

[0021] Figure 2 Shown are the XRD patterns of the films deposited at different potentials at 30 °C (-0.3 V to -0.7 V).

[0022] Figure 3 Shown are the XRD patterns of the films deposited at different potentials at 30 °C (-0.8 V to -1.2 V). DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0024] In order to analyze the electrodeposition process of the film, the effect of different complexing agents on the solution was studied by cyclic voltammetry. Disodium EDTA, oxalic acid, sodium citrate and potassium sodium tartrate were selected as complexing agents, respectively, and tested with a CHI760e electrochemical workstation at room temperature. A platinum electrode was used as an auxiliary level, a platinum electrode was used as an auxiliary electrode, and a SCE saturated calomel electrode (KCl) with about +0.245V was used as a reference electrode. The scanning voltage range was +0V to -1.0V, and a negative scan was performed first, followed by a positive scan, with a scan rate of 10mV / s.

[0025] Highly oriented CuFeTe for solar cells 2 The method for preparing a thin film is characterized by comprising the following steps: FTO substrate cleaning step and electrodeposition solution preparation step: the electrodeposition solution comprises; Constant potential deposition step: under atmospheric pressure, the FTO base is placed in an electrodeposition solution for electrodeposition using a constant potential three-electrode system, and the deposition temperature, deposition time and deposition potential are preset, and the deposition potential is -1.0V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing steps: The sample treated by the constant potential deposition step is immersed in deionized water for 3 times, then taken out and annealed at a preset temperature and a preset time to prepare CuFeTe 2 film.

[0026] FTO base cleaning includes: S1: Use medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the beaker mouth is wrapped with plastic wrap and sealed. The steps of preparing the electrodeposition solution are to weigh the drug using an analytical balance, dissolve tellurium dioxide in hydrochloric acid, use a magnetic stirrer, stir and dissolve while heating to accelerate its dissolution, and after the dissolution is completed, add deionized water to the preset scale, and then add sodium citrate, FeCl2 and CuSO4, fully dissolve, and finally obtain the electrodeposition solution.

[0027] In some specific embodiments, the deposition time of the constant potential deposition step is 20 min.

[0028] In some specific embodiments, the deposition temperature of the constant potential deposition step is 30° C., and the deposition time is 20 min.

[0029] In some specific embodiments, the deposition temperature of the constant potential deposition step is 50° C., and the deposition time is 20 min.

[0030] In some specific embodiments, CuFeTe 2 The thickness of the film was 20 μm.

[0031] In some specific embodiments, the deposition temperature of the constant potential deposition step is 90° C., and the deposition time is 20 min.

[0032] In some specific embodiments, in the annealing step, the preset temperature is 200° C., and the preset time is 30 hours.

[0033] A highly oriented preparation method for solar cells, the sequence is: conductive oxide glass substrate, ZnO layer, TiO2 electron transport layer, P-type CuFeTe 2 Absorption layer, hole transport layer and back electrode layer; the thickness of TiO2 electron transport layer is 70nm-90nm, P-type CuFeTe 2 The thickness of the absorption layer is 20 μm. The conductive oxide glass substrate is FTO conductive glass or ITO ultra-white glass.

[0034] The hole transport layer is prepared by spin coating, including: dissolving Spiro-OMeTAD in chlorobenzene, adding 4-tert-butylpyridine and Li-TFSI acetonitrile solution and stirring until the solution is clear and transparent, and spin coating the prepared Spiro-OMeTAD solution on the P-type CuFeTe 2 The surface of the absorption layer is then placed on a heating plate and heated at 110°C in air for 15 minutes. The material of the back electrode layer is gold, and the thickness of the back electrode layer is 80nm-90nm. P-type CuFeTe 2 The thickness of the absorption layer is 20 μm, P-type CuFeTe 2 The absorber layer was deposited on TiO 2 Surface of electron transport layer. Conductive oxide glass substrate, ZnO layer, TiO 2 Electron transport layer, P-type CuFeTe 2 Absorption layer, hole transport layer and back electrode layer.

[0035] Preparation of ZnO layer: a 80nm-85nm ZnO electron transport layer was deposited by sol-gel method; TiO 2 Preparation of electron transport layer: 70uL of dilute hydrochloric acid and 700uL of isopropyl titanate were added to 5ml of ethanol respectively, and then mixed together to obtain TiO 2 The solution was thoroughly mixed and shaken, and then filtered for use; the filtered TiO 2 The solution was statically dropped onto the ZnO layer, spin-coated at 2000 rpm for 30 s, and annealed at 150°C, 250°C, and 350°C for 10 min each, and finally annealed at 550°C for 30 min to obtain an electron transport layer (TiO2) film with a thickness of about 50 nm; P-type CuFeTe 2 The absorber layer was prepared by electrodeposition.

[0036] like Figure 1As shown in the figure, when the deposition potential is -1.0 V, the XRD patterns of the films with different deposition times (10 min to 30 min) show that the 101 peak intensity is higher when the deposition time is 20 min than when the deposition time is 10 min and 30 min. 2 The film forms a preferred orientation on the (101) crystal plane, which significantly improves the crystal structure of the film, making the film continuous and dense within a certain range, and achieving the best deposition effect. Therefore, by controlling the deposition time under the same deposition voltage, a better deposition effect can be obtained.

[0037] like Figure 2 and Figure 3 The following are XRD patterns of samples that were electro-deposited and then retreated at different deposition potentials when the deposition temperature was 30°C and the deposition time was 20 min. Figure 2 and Figure 3 It can be seen that when the deposition potential is -0.6 V, CuFeTe 2 The diffraction peak of CuFeTe gradually appears, and the diffraction peak gradually increases with the negative shift of the deposition potential. 2 The diffraction peak of CuFeTe2 did not appear when the deposition potential was -0.9V. When the deposition potential was -1.0V, the diffraction peak intensity reached the maximum value and then gradually decreased. Corresponding to the standard spectrum (PDF standard card No. 70-3094), the diffraction peak of CuFeTe2 grew along the (101), (112) and (211) crystal planes, and the diffraction angles were 2θ=26.975°, 44.097° and 54.233°, respectively. The film formed a preferred orientation on the (101) crystal plane. In addition to the target product CuFeTe2, the diffraction peak of SnO2 was also found (PDF standard card No. 46-1088). At the same time, with the negative shift of the deposition potential, the hydrogen evolution phenomenon will be aggravated, it is not easy to form a continuous film, the porous bonding force of the film is poor, and black particles appear near the working electrode and are suspended on the surface of the solution. Therefore, when the deposition temperature is 30℃, the deposition time is 20min, and the deposition potential is -1.0V, the deposition effect is best.

[0038] Furthermore, when the deposition temperature is 50 °C and the deposition time is 20 min, the samples electrodeposited at different deposition potentials and then heat treated have CuFeTe 2 The peak diffraction value gradually appears at the deposition potential of -0.6V and -0.7V. The diffraction peak of the film increases with the negative shift of the deposition potential, and the deposition voltage is the largest at -1.0V. Corresponding standard spectrum (PDF standard card number 70-3094), CuFeTe 2 The diffraction peaks of the film grow along the (101), (112) and (211) crystal planes, with diffraction angles of 2θ=26.975°, 44.097° and 54.233°, respectively. The film forms a preferred orientation on the (101) crystal plane.2 In addition, the diffraction peak of SnO2 was also found (PDF standard card No. 46-1088). Therefore, the deposition effect is best when the deposition temperature is 50℃, the deposition time is 20min, and the deposition potential is -1.0V.

[0039] Therefore, by controlling the deposition potential to -1.0 V, the CuFeTe2 film forms a preferred orientation on the (101) crystal plane, which significantly improves the crystal structure of the film, makes the film continuous and dense within a certain range, and achieves the best deposition effect.

[0040] Furthermore, by preparing CuFeTe 2 Thin-film solar cells can effectively improve their performance because the higher the film orientation, the better the performance of the solar cell.

[0041] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a highly oriented CuFeTe2 thin film for solar cells, characterized in that: The steps include: FTO substrate cleaning step and electrodeposition solution preparation step: the electrodeposition solution comprises; Constant potential deposition step: under atmospheric pressure, the FTO base is placed in an electrodeposition solution for electrodeposition using a constant potential three-electrode system, and the deposition temperature, deposition time and deposition potential are preset, and the deposition potential is -1.0V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing steps: soak the sample processed by the constant potential deposition step in deionized water, then take it out and anneal it at a preset temperature and a preset time to prepare a CuFeTe2 film.

2. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The FTO base cleaning includes: S1: Use a medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the mouth of the beaker is wrapped with plastic wrap and sealed.

3. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The steps of preparing the electrodeposition solution are as follows: weighing the drug using an analytical balance, dissolving tellurium dioxide in hydrochloric acid, using a magnetic stirrer to heat and stir the solution to accelerate its dissolution, adding deionized water to a preset scale after the solution is completed, and then adding sodium citrate, FeCl2 and CuSO4 to fully dissolve the solution to obtain the electrodeposition solution.

4. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition time of the constant potential deposition step is 20 min.

5. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition temperature of the constant potential deposition step is 30° C., and the deposition time is 20 min.

6. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition temperature of the constant potential deposition step is 50° C. and the deposition time is 20 min.

7. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The thickness of the CuFeTe2 film is 20 μm.

8. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition temperature of the constant potential deposition step is 90° C., and the deposition time is 20 min.

9. The method for preparing a highly oriented CuFeTe2 thin film for solar cells according to claim 1, characterized in that: In the annealing step, the preset temperature is 200° C. and the preset time is 30 hours.